The impact of systemic diseases - Diabetes, Cardiovascular diseases, Epilepsy, Thyroid diseases, on the condition of the oral cavity and the course of a dental visit - Czapska, Mirella; Krygicz, Kamila; Kocoń, Marcin; Krawczyk, Lidia; Duplaga, Tomasz; Babkiewicz-Jahn, Kamila; Matuszewska, Justyna; Szymańska , Adrianna (Quality in Sport, 2024)
Introduction and purpose.Systemic diseases are affecting an increasing number of people worldwide. Both adults, the elderly, and children are affected. Social awareness regarding diseases and their symptoms remains very low. In the rush of life, we forget how important it is to take care of our health to fully enjoy each day. Many systemic diseases exhibit characteristic symptoms in the oral cavity. Patients are often unaware of this, which emphasizes the importance of alertness on the part of the dental practitioner, thorough history-taking not only in dentistry but also in general medicine, and comprehensive patient examination. Patient awareness of their condition not only matters for the individual but also significantly impacts the course of the dental visit, office preparation, and procedures performed. Many diseases, especially those uncontrolled, may preclude certain treatments or necessitate alterations in dental management. Materials and methods. The article presents the current state of knowledge regarding the impact of systemic diseases on the condition of the oral cavity in various scientific publications. Publications describing these diseases and the course of dental visits were reviewed using the PubMed platform and included in textbooks listed in current scientific databases. Conclusions. Awareness of the oral cavity's condition, as well as the symptoms that systemic diseases can exhibit, has a tremendous impact on our health. Early detection of pathologies and implementation of treatment contribute to halting or slowing down the progression of the disease, as well as improving our well-being. Increasing patient awareness of the significance of lifestyle, regular check-ups, prevention, and lifestyle choices can influence an individual's future and eventually raise awareness across society.